Ultrasound evaluation of percutaneously created arteriovenous fistulae between radial artery and perforating vein at the elbow. Issue 5 (September 2020) - Franco, Gilbert; Mallios, Alexandros; Bourquelot, Pierre; Jennings, William; Boura, Benoit
Objective: To investigate the hemodynamics of percutaneous arteriovenous fistulae (pAVF) created between the proximal radial artery and the deep communicating vein of the elbow. Methods: Consecutive patients with a percutaneously created proximal radial artery to perforating vein arteriovenous fistulae were evaluated and compared with control patients with clinically well-functioning surgical wrist radiocephalic arteriovenous fistulae (sWRC-AVF). Results: Thirty-one patients with a pAVF (21 males – 68%, mean age: 62 years, range: 53–81), with mean follow-up of 254 days (range: 60–443) and 32 patients with a surgical fistula (20 males – 62%, mean age of 63 years, range: 30–84) were evaluated. Mean access flow and distribution range were similar in the two study groups, with a mean flow of 859 mL/min vs 919 mL/min, respectively. There was no significant difference in the mean radial artery diameter (4 mm vs 4.3 mm, p = 0.2). Statistically significant trends were observed for resistive index (0.57 pAVF vs 0.52 (0.07) and brachial vein cross-sectional area (13 pAVF vs 33 mm 2, p = 0.06). The arteriovenous anastomosis area was significantly smaller with pAVFs (13 vs 43 mm 2, p = 0.002) and the pressure difference between extremities was less for the pAVF group vs sWRC-AVF (19 vs 27 mm Hg, respectively, p = 0.03). Existence of single cephalic or basilic versus cephalic and basilic outflow did not affect vein maturation or overall flow. Conclusions: pAVF have a favourable hemodynamic profile with many similarities when compared with surgically created wrist fistulae. Cephalic and/or basilic vein matured with only minor outflow shunted to the deep venous system.